GNSS-Acoustic Observations of Seafloor Crustal Deformation Using a Wave Glider - Iinuma, Takeshi; Kido, Motoyuki; Ohta, Yusaku; Fukuda, Tatsuya; Tomita, Fumiaki; Ueki, Iwao (Frontiers in Earth Science, 2021)
Crustal deformation of the seafloor is difficult to observe solely using global navigation satellite system (GNSS). The GNSS-acoustic (GNSS-A) technique was developed to observe seafloor crustal deformation, and it has produced a steady series of successful observations with remarkable results related to crustal deformation associated with huge earthquakes around the Japanese Islands. However, utilizing GNSS-A incurs very large financial and human costs as it requires the use of a research vessel as a surface platform and has a limited observation frequency, which is less than once a year at seafloor stations along the Japan Trench. To conduct frequent observations, an automatic GNSS-A data acquisition system was developed that operates via an unmanned surface vehicle (wave glider). The first observations using this system were performed at a seafloor station off Aomori Prefecture in July 2019. The wave glider was equipped with two GNSS antennas, an acoustic transducer, a microelectromechanical system gyroscope, and associated control and logging units. Data acquisition and autonomous activation of the seafloor stations were successfully executed by controlling the power supply to the payload via satellite communication with the wave glider. The glider rarely strayed off the configured course and the solar panels generated sufficient power to perform the observations although the weather was mostly cloudy. The GNSS-A data processing results show that the position of the station was determined with the same accuracy and precision as in previous observations performed using a research vessel.